Anti-Inflammatory MicroRNAs and Their Potential for Inflammatory Diseases Treatment - Tahamtan, Alireza; Teymoori-Rad, Majid; Nakstad, Britt; Salimi, Vahid (Frontiers in Immunology, 2018)
Inflammation is a complicated biological and pathophysiological cascade of responses to infections and injuries, and inflammatory mechanisms are closely related to many diseases. The magnitude, the complicated network of pro- and anti-inflammatory factors, and the direction of the inflammatory response can impact on the development and progression of a variety of disorders. The currently available treatment strategies often target the symptoms and not the causes of inflammatory disease and may often be ineffective. Since the onset and termination of inflammation are crucial to prevent tissue damage, a range of mechanisms has evolved in nature to regulate the process including negative and positive feedback loops. In this regard, microRNAs (miRNAs) have emerged as key gene regulators to control inflammation, and it is speculated that they are fine-tune signaling regulators in order to allow for proper resolution and prevent uncontrolled progress of inflammatory reactions. In this review, we discuss recent findings related to significant roles of miRNAs in immune regulation, especially the potential utility of these molecules as novel anti-inflammatory agents to treat inflammatory diseases. Furthermore, we discuss the possibilities of using miRNAs as drugs in the form of miRNA mimics or miRNA antagonists.